Application of extended elastic impedance (EEI) inversion to reservoir from non-reservoir discrimination of Ghar reservoir in one Iranian oil field within Persian Gulf. (18th April 2018) - Alebouyeh, Mohsen; Chehrazi, Ali
Abstract: The aim of this study is to discriminate reservoir from non-reservoir facies of the Ghar formation in one Iranian oil field within the Persian Gulf, using extended elastic impedance (EEI) inversion. The Ghar reservoir, as a member of the Asmari Formation, consists of reservoir unites with interbedded shales. It is often difficult to separate these units. The lithological facies discrimination of the Ghar reservoir was applied, using the simultaneous application of EEI attributes. The EEI inversion method used best χ angles from cross-correlation based on a model-based inversion algorithm to generate the EEI attributes. In the facies discrimination, the lithological facies volume was provided based on EEI Lambda-Rho versus EEI Mu-Rho cross-plot mapping together with porosity, water saturation, shale volume, sand volume and dolomite volume, which attributes indicated good definition of the reservoir unites with low values. The volume of the facies discrimination presented excellent separation of lithological facies, consistent with the well logs with petro-physical interpretations. As a result of this study, three facies in several stratigraphic levels of the Ghar reservoir were identified: sandstone facies, dolomite-sandstone facies (tight and porous), and shaly facies. As a result, the middle part of the Ghar reservoir was identified as the most porous reservoir unite, consistent with lower EEI Lambda-Rho and EEI Mu-Rho values. Since all the well locations were drilled in the southern part of this field, the results can be practical for well location drilling and field development in the northern part of the field.